Limonene formulation exhibited potential application in the control of mycelial growth and deoxynivalenol production in Fusarium graminearum - Jian, Yunqing; Chen, Xia; Ma, Haiqin; Zhang, Changpeng; Luo, Yuqin; Jiang, Jinhua; Yin, Yanni (Frontiers in Microbiology, 2023)
Preventing grain from fungi and subsequent mycotoxins contamination has attracted notable attention. Present study demonstrated the limonene-formulated product Wetcit®, might be a biocontrol agent and potential alternative to synthetic fungicides to control Fusarium graminearum growth and deoxynivalenol (DON) production. The limonene formulation exhibited antifungal activity against F. graminearum with the EC50 at 1.40 μL/mL, electron microscopy and staining analysis showed limonene formulation could significantly decreased the quantity, length and septa of conidia, caused hyphal break and shrink, damaged the structures of cell membrane, cell wall, vacuoles and organelles in the hypha. Further study revealed the antifungal and antitoxic mechanism of limonene formulation against F. graminearum, limonene formulation significantly inhibited the toxisome and DON formation, was associated with the down-regulation of trichothecenes biosynthesis genes expression and many energy metabolism pathways as well as the inhibition of lipid droplets, the disturbed energy homeostasis and intracellular structures might ultimately inhibit fungal growth and DON production. In addition, limonene formulation enhanced the antifungal activity of triazole fungicides tebuconazole and mefentrifluconazole against F. graminearum, indicated limonene formulation has valuable potential as a bio-alternative fungicide and eco-friendly compound preparation for the effective management of F. graminearum and DON contamination in agriculture.